Single-Layer Drying Behavior of Red Chili - Junaedi Muhidong; Supratomo Supratomo; Nur Ftiri Ramadhani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
This study was designated to determine the best model that could represent the behavior of the moisture content of cut red-chili, Tombak variety, during the single layer drying process. A Tray Dryer Model EH-TD-300 Eunha Fluid Science was used to support the experiment. The dryer was constructed to flow the drying-air parallel with the crop observed. Three levels of drying air velocity (1.0 m/s, 1.5 m/s, and 2.0 m/s) were applied under a constant drying air temperature of 47oC. The average relative humidity (RH) in the drying chamber during the drying period was around 39%. The results of this study strongly suggested that the Hii et al. (2008) model, MR = 0.76832.exp(-0.06607.t1.43089) + 0.25351.exp(-0.06881.t1.43089) and MR = 0.76758.exp(-0.10141.t1.47651) + 0.30562.exp(-0.10018.t1.47651), were the best model in predicting the moisture behavior of the cut chili, Tombak variety, across the elapsed drying time when the drying air velocities were set to 1.5 m/s and 2.0 m/s, respectively. However, the Diffusion Approach model, MR = -0.02821.exp(0.01340.t) + (1.02821)).exp(-0.107576.t), was observed to be the best model at the drying air velocity of 1.0 m/s.